Patient-elected low-dose intravenous naloxone for rapid buprenorphine induction: a case report - Pouya Azar; Jessica Machado; Jane J. Kim; James S. H. Wong; Mohammadali Nikoo; Victor W. Li (Addiction Science & Clinical Practice)
Abstract Background Buprenorphine is a common partial opioid agonist treatment for opioid use disorder (OUD). Despite its efficacy, major challenges to induction include the significant time consumption and the difficult requirement for patients to be in moderate opioid withdrawal. Case presentation We present the case of a 31-year-old man with severe OUD and regular fentanyl use who was successfully initiated on buprenorphine-naloxone using low-dose intravenous naloxone in ten minutes and administered 300 mg of extended-release injectable buprenorphine within two hours. This involved the rapid administration of small doses of intravenous naloxone with an assessment of withdrawal symptoms after each dose. Buprenorphine-naloxone is immediately administered once moderate withdrawal is reached. Conclusions Low-dose intravenous naloxone provides an alternative method of buprenorphine induction that limits the experience of withdrawal to a shorter time window compared to existing protocols.